5 - Broadening Perceptions and Parameters for Quality Assurance in University Operations in Uganda - Barymak, Rita Makumbi; Kakembo, Frederick (Journal of Higher Education in Africa, 2022)
This article explores the stakeholders’ perceptions of quality in university operations in Uganda, specifically in terms of the core functions of teaching, research and community engagement. Conceptually, universities aim to transform, modernise and develop science and technology. A review of the literature suggests that many university communities are an elite group of professors and students who live in relative isolation. Within this ‘protective environment’ occurs a significant research milieu which is more basic than applied and, thereby, not relevant to local systems and somewhat foreign to community members. Further, the linkage between research results and institution policy makers is minimal or non-existent. In light of this background, it is argued that typical quality assurance (QA) initiatives in many universities focus on establishing operational efficiency of conventional structures of teaching and research. The study investigates comprehensiveness of parameters used by various stakeholders to determine quality in and of university education. Making reference to community engagement as one of the universities’ core functions, this study investigates whether community issues and social welfare are central in the conceiving, planning and implementing QA initiatives. Qualitative and quantitative approaches were used to generate data; specifically, questionnaires, interviews, content analysis of academic and non-academic programme and documents reviews were analysed. Preliminary findings reveal a stronger focus on conventional teaching and scholarly research than on community engagement initiatives. Conceptualisation of a quality university education by various stakeholders (students, lecturers, administration, parents and policy makers) is influenced by concerns of effectiveness and regularity of activities at the universities. Monitoring and evaluation activities emphasise: a) effectiveness of teaching and learning; b) relevancy of academic programmes to job-markets; c) quality of basic research; d) number of publications in accredited international journals; and e) concerns regarding ranking of the university relative to others in the country, region, continent and the globe. A lack of emphasis on community engagement initiatives could be explained by the fact that a number of practitioners could be products of the same existing structures and may not be in position to detect the discrepancies. Conversely, local communities, within which these institutions operate as expected immediate beneficiaries, often perceive universities as abstract institutions for the super-elite, and that the ‘ivory tower’ has little applicability to the day-to-day lives of grassroots communities. It is proposed that debates and dialogues should be organised to engage various stakeholders in re-definition of expectations, duties and responsibilities of higher education in relation to community engagement.